2021
DOI: 10.7717/peerj.10893
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Polar Vantage M watch when measuring heart rate at different exercise intensities

Abstract: Background The use of wrist worn wearable fitness trackers has been growing rapidly over the last decade. The growing popularity can be partly attributed to the improvements in technology, making activity trackers more affordable, comfortable and convenient for use in different fitness and environmental applications. Fitness trackers typically monitor activity level, track steps, distance, heart rate (HR), sleep, peripheral capillary oxygen saturation and more, as the technology continuously is advancing. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…0.74), while for stages 3-5 that corresponded to high intensity, the device showed poor validity (ICC \ 0.50). 23 In relation to the results of the present study, a greater level of agreement was found (ICC . 0.94), despite using different reference systems (Polar H10 vs EKG).…”
Section: Discussionsupporting
confidence: 73%
“…0.74), while for stages 3-5 that corresponded to high intensity, the device showed poor validity (ICC \ 0.50). 23 In relation to the results of the present study, a greater level of agreement was found (ICC . 0.94), despite using different reference systems (Polar H10 vs EKG).…”
Section: Discussionsupporting
confidence: 73%
“…The primary goals were to determine total workload, estimate caloric expenditure, and document injury rates in female recruits. It is acknowledged that wearables estimate caloric expenditure on the basis of heart rate; however, Polar heart rate monitors have been validated in multiple efforts [ 41 , 42 , 43 ], and the use of wearable technology in field data collection has become widely accepted [ 44 , 45 , 46 , 47 ]. Additionally, menstrual cycle history was collected as part of basic health history but was not an initial focus.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac signals were mostly measured with different versions of the Polar heart rate monitor [100] (eight studies [40,49,65,67,68,[70][71][72]), while ActiGraph [101] and Fitbit [102] accelerometers were found in three studies each ([53,62,73] and [70,74,75], respectively) to report physical activity characteristics. Regarding core temperature monitoring, ingestible thermometer pills were used in three studies [51,65,73].…”
Section: Physiological Monitoring Systems and Processing Methodsmentioning
confidence: 99%